2020
DOI: 10.22541/au.159714891.13637598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional impact of Covid-19 pandemic on children and parents with problematic severe asthma

Abstract: Clinical Implications: this is the first study describing the impact of COVID-19 /lockdown on the psychological and emotional wellbeing in a selected group of children with problematic severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…32 Although these surveys did not differentiate whether concern about return to in-person learning was associated with perceived risk of chronic conditions such as asthma, a recent survey found that the majority of parents of school-aged children with asthma (64%) were worried about an asthma exacerbation during COVID-19, also poignantly noting that emotional well-being had impacted asthma control. 33 A clearer understanding of the motivation and beneficiaries of the decision to keep a child out of in-person school is needed.…”
Section: The Perceived Risk Of In-school Learning Among Families Of Children With Asthmamentioning
confidence: 99%
“…32 Although these surveys did not differentiate whether concern about return to in-person learning was associated with perceived risk of chronic conditions such as asthma, a recent survey found that the majority of parents of school-aged children with asthma (64%) were worried about an asthma exacerbation during COVID-19, also poignantly noting that emotional well-being had impacted asthma control. 33 A clearer understanding of the motivation and beneficiaries of the decision to keep a child out of in-person school is needed.…”
Section: The Perceived Risk Of In-school Learning Among Families Of Children With Asthmamentioning
confidence: 99%
“…1 Yapılan çalışmalarda ailelerin yüz yüze öğrenmeye geri dönmekten endişe duydukları, 8 sanal öğrenmeyi tercih ettikleri, 9 ayrıca okul çağındaki astımlı çocukların çoğunun astım konusunda endişelendiği belirlenmiştir. 10 Pandemi sürecinde ülkeler, hastaları test ve tedavi ederek, temaslı kişilerin takibini yaparak, seyahatleri sınırlandırarak, vatandaşlarını karantinaya alarak ve spor etkinlikleri, konserler ve okullar gibi büyük toplantıları iptal ederek hastalığın yayılmasını yavaşlatmaya çalışmaktadır. 2 Ayrıca sosyal mesafe, eğitime ara verilmesi ya da eğitimin uzaktan sürdürülmesi gibi çeşitli değişimler ve dönüşümler de yaşanmaktadır.…”
Section: Introductionunclassified